Alternative splicing and nonsense-mediated RNA decay contribute to the regulation of SHOX expression - Durand, Claudia; Röth, Ralph; Dweep, Harsh; Vlatkovic, Irena; Decker, Eva; Schneider, Katja U.; Rappold, Gudrun (PLOS ONE, 2011)
The human SHOX gene is composed of seven exons and encodes a paired-related homeodomain transcription factor. SHOX mutations or deletions have been associated with different short stature syndromes implying a role in growth and bone formation. During development, SHOX is expressed in a highly specific spatiotemporal expression pattern, the underlying regulatory mechanisms of which remain largely unknown. We have analysed SHOX expression in diverse embryonic, fetal and adult human tissues and detected expression in many tissues that were not known to express SHOX before, e.g. distinct brain regions. By using RT-PCR and comparing the results with RNA-Seq data, we have identified four novel exons (exon 2a, 7-1, 7-2 and 7-3) contributing to different SHOX isoforms, and also established an expression profile for the emerging new SHOX isoforms. Interestingly, we found the exon 7 variants to be exclusively expressed in fetal neural tissues, which could argue for a specific role of these variants during brain development. A bioinformatical analysis of the three novel 3′UTR exons yielded insights into the putative role of the different 3′UTRs as targets for miRNA binding. Functional analysis revealed that inclusion of exon 2a leads to nonsense-mediated RNA decay altering SHOX expression in a tissue and time specific manner. In conclusion, SHOX expression is regulated by different mechanisms and alternative splicing coupled with nonsense-mediated RNA decay constitutes a further component that can be used to fine tune the SHOX expression level.
Gesehen am 31.03.2022